Studi Deskriptif Pengetahuan dan Dukungan Suami tentang Pemilihan Alat Kontrasepsi Suntik pada Pasangan Usia Subur di Puskesmas Larangan Kabupaten Brebes - Intan Monik Pratami (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2020)
Indonesia is currently enjoying a demographic bonus period where the number of productive age population is more than non-productive age, which is more than 68% of the total population. In this case the government through BKKBN try to improve family planning services as it is expected to prevent the explosion of population by means of family planning (KB). There are various types of contraception, one of them is injection. Its high effectiveness can be relied upon as a contraceptive method so the number of acceptors is very high compared to other methods. There are various factors that influence, among others, the level of knowledge and support of the husband. 3-month injection contraception is a contraceptive in the form of a liquid that contains only the hormone progesterone and is injected into a woman's body periodically that is 3 months (MOH RI. 2002). Based on the Research Results 35 respondents (100%) Injecting KB acceptors, 9 respondents (25.72%) with high knowledge, medium knowledge 11 respondents (31.43%), low knowledge 15 respondents (42.85%). Husbands who gave support were 20 respondents (57.115%) and those who did not support 15 respondents (42.85%). Health workers played an important role in providing information about Family Planning methods for prospective acceptors, in this case specifically fertile age couples. Provision of this information is done through counseling using KB Decision-Making Aids (ABPK).